Adapting to the future: examining the impact of transport automation and digitalization on the labor force through the perspectives of stakeholders in all transport sectors - Polydoropoulou, Amalia; Thanopoulou, Helen; Karakikes, Ioannis; Pronello, Cristina; Tyrinopoulos, Yannis (Frontiers in Future Transportation, 2023)
Automation in transport and digitalization will affect both transport users and its workforce. Focusing on the latter, this paper aims at analyzing barriers, gaps, opportunities, and success and failure factors of transport automation on the labor force, through the perceptions and contributions of employees and employers, as well as of stakeholders from the private, public, and private-public sectors. In a nutshell, the study aims to understand workforce-related barriers and facilitators associated with the implementation of automation. This has been achieved through input derived from the organization of five focus groups, one poll and one extensive questionnaire survey questionnaire administered to the participants of the 2nd WE-TRANSFORM EU H2020 funded project Workshop and to project partners’ stakeholder contacts. The analysis of the results indicated that the transport sector’s automation has been evolving at a different pace per sector. An interesting conclusion is that any challenges do not concern all categories among the workforce in the same way. Challenges related to loss of jobs and related repercussions are bound to affect groups within the workforce which may be constrained by regulatory age limits, or vulnerable, if in part-time employment without access to retraining which may be the case of workforce members near retirement age or of women limited due to family obligations to part-time employment. The study's limitations are related to the size of the sample and how representative it is of all stakeholders in the transport sector, including policymakers, regulators, and unions. Future directions should focus on exploring the long-term impacts of automation on the labor force and identify strategies to mitigate the negative effects on vulnerable groups.